Design and Realization of Universal Data Interface - Jong-Woo Kim; Suk-Bae Seo; Kyung-Taek kim (Journal of Astronomy and Space Sciences, 2005)
KARI studied data interface of Space Applications for developing Space Experimental Instrument in International Space Station, designed, and manufactured the UDIS (International Sapce Station Universal Data Interface simulator) according to requirements of the data interface. This paper explains the design and implementation of UDIS for space application. UDIS is the instrument which simulate to interface the data from ISS to experiment module, payload and habitation module and use the development of a experiment system in the space. This simulator will be used to the GSE (Ground Support Equipment) for test of experiment system. By realization of the simulator, we ensure data interface skills for a manned-space data communication system.